FORMULASI / MODEL SISTEM PEMIDANAAN ANAK DI INDONESIA - Ahmad Syakirin (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
Criminal systems that are restorative Justice must be the priority of the judge in making decisions. Placing a child in prison is always the last choice and with the shortest possible period of time. Placing children in institutions that have social benefits and functions as well as improvements for children, Children have the potential for growth in the future, so that children should be given guidance, care, education, and protection, as well as skills, both physically, mentally, and socially . Therefore a child who commits a crime is required by a child-only court. The child punishment system must pay attention to the interests of the child and in accordance with the standards of value and treatment of a number of national and international instruments. Diversion and the concept of Restorative justice need to be taken into consideration in handling child cases. This concept involves all parties in order to improve children's morale so that they do not repeat their actions anymore, and children do not feel like a prisoner that affects the child's mental development.